TERRA Latinoamerica, half a century of history - Castellanos-Ramos, Javier Z.; Etchevers-Barra, Jorge Dionisio (REVISTA TERRA LATINOAMERICANA, 2022)
Dear SMCS Colleagues: Dr. Jorge Etchevers and a server thought it was a good idea to document the effort made by each of the editors of Terra Latinoamericana magazine to get where you arrived. A 50-year effort is easy to write, but it has been an epic, since its foundation by Dr. Antonio Turrent Fernández, who with great dedication and effort laid the foundations to achieve the magazine. Colleagues like Dr. Mario Martínez Menes helped us from the spheres of government in the most difficult moments of the magazine. All the editors played a key role in keeping the magazine alive and thriving. To these editors we owe a lot to the researchers in the area of soil science and naturalresources. In this order of ideas, we take the liberty of asking the editors for the testimony of their work in order to get where this scientific journal has come, which is already very close to being accepted into the JCR, which will become a magazine of international stature. We consider that because they are two important pillars in the magazine and that they played an important role in it, we decided to include the testimonies of our beloved Ina Aalmers and Rosa María López Atilano. It is worth reading the testimonials of each editor. Go to all of us with our eternal gratitude. Dr. Javier Z. Castellanos Ex–Presidente SMCS, 2019-2021